Formulation of Online Dispute Resolution in Realizing Fair Industrial Relations Dispute Settlement: A Comparative Study - Kadek Agus Sudiarawan; Yasa, Putu Gede Arya Sumerta; Desak Putu Dewi Kasih; Nyoman Satyayudha Dananjaya; Ni Ketut Devi Damayanti (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
Although alternative method exists as stipulated in Article 3 paragraph (1) and Article 4 paragraph (3) of the Industrial Relations Dispute Settlement Law, in fact, the dispute resolution in Indonesia’s industrial relation has been focusing on litigation mechanisms. However, litigation is not the best way to fulfill both disputing parties’ desire for justice as the output is win-lose. As such, alternative method exists, puts forward the ‘win-win’ solution. Nonetheless, the current legal framework only sets the clear rule of the aforementioned alternative method to be conducted in person, despite the global pandemic Covid-19. Accordingly, ODR is established to enable virtual procurement. This article will analyze the conception and benefits of online dispute resolution, its implementation gaps in the context of industrial relations dispute resolution, and its regulatory formulation to gain legitimacy in Indonesian law. Applying normative legal research, this article uses statutory, conceptual and comparative approaches. From the research conducted, it is indicated that online dispute resolution is technically superior as it is simple, fast, and low in cost. Even under the Industrial Relations Dispute Settlement Law, its application is feasible, specifically through mediation and conciliation. In Indonesia, implementation of online dispute resolution is possible by amending the Industrial Relations Dispute Settlement Law, considering the prioritization of alternative dispute resolution based on practices in Cambodia, Spain, and ILO Guidelines, as well as the superiority of online dispute resolution based on practices in the United States and UNCITRAL Technical Notes.